1999
DOI: 10.1002/chp.1340190205
|View full text |Cite
|
Sign up to set email alerts
|

Continuing education credit hours taken by general practice dentists

Abstract: One of the goals of continuing education (CE) is to enhance lifelong learning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…half-day, full-day) differ or are not specified. Furthermore, although the majority of these studies looked at courses undertaken in the previous year (4,25,31,33,34,(39)(40)(41)43), some looked over a 2-year period (28,29,35,36) and one considered intentions (10). Review of CPD for dentists Barnes et al To understand more about the reasons for the variation in engagement with CPD, studies that reported factors relating to CPD uptake were scrutinised.…”
Section: Continuing Professional Development Uptakementioning
confidence: 99%
“…half-day, full-day) differ or are not specified. Furthermore, although the majority of these studies looked at courses undertaken in the previous year (4,25,31,33,34,(39)(40)(41)43), some looked over a 2-year period (28,29,35,36) and one considered intentions (10). Review of CPD for dentists Barnes et al To understand more about the reasons for the variation in engagement with CPD, studies that reported factors relating to CPD uptake were scrutinised.…”
Section: Continuing Professional Development Uptakementioning
confidence: 99%
“…half-day, full-day) differ or are not specified. Furthermore, although the majority of these studies looked at courses undertaken in the previous year (4,25,31,33,34,(39)(40)(41)43), some looked over a 2-year period (28,29,35,36) and one considered intentions (10). To understand more about the reasons for the variation in engagement with CPD, studies that reported factors relating to CPD uptake were scrutinised.…”
Section: Continuing Professional Development Uptakementioning
confidence: 99%
“…The distance from the place of CE activities, attendance-related expenses, type of CE courses, and instructional methods are important elements when planning CE activities [ 4 ]. The cost of continuing professional courses, the distance or the location of a course, the loss of work, and courses not relevant were the barriers to attending educational courses for general dentists [ 5 ].…”
Section: Introductionmentioning
confidence: 99%